2018
DOI: 10.1111/epi.13998
|View full text |Cite
|
Sign up to set email alerts
|

Sudden unexpected death in epilepsy in patients treated with brain‐responsive neurostimulation

Abstract: and an electrographic and witnessed seizure with cessation of postictal electrocorticography (ECoG) activity associated with apnea and pulselessness (n = 1). Significance: The SUDEP rate of 2.0/1000 patient stimulation years among patients treated with the RNS System is favorable relative to treatment-resistant epilepsy patients randomized to the placebo arm of add-on drug studies or with seizures after resective surgery. Our findings support that treatments that reduce seizures reduce SUDEP risk and that not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 15 publications
0
49
0
2
Order By: Relevance
“…Establishment of nonseizure SUDEP as an entity 38 suggests that brainstem dysfunction may initiate the agonal event independently of cortical seizures. 39,40 Whereas spreading depression in cardiorespiratory suppression is unproven in humans, increasing evidence from imaging 41,42 and pathologic studies 43 suggests that key cardiorespiratory control structures are significantly damaged in patients with intractable epilepsy who succumb to SUDEP. Imaging studies 42 have shown increased right hippocampal and parahippocampal gray matter volume in patients experiencing SUDEP and high-SUDEP-risk patients, setting the stage for possible autonomic and respiratory output dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Establishment of nonseizure SUDEP as an entity 38 suggests that brainstem dysfunction may initiate the agonal event independently of cortical seizures. 39,40 Whereas spreading depression in cardiorespiratory suppression is unproven in humans, increasing evidence from imaging 41,42 and pathologic studies 43 suggests that key cardiorespiratory control structures are significantly damaged in patients with intractable epilepsy who succumb to SUDEP. Imaging studies 42 have shown increased right hippocampal and parahippocampal gray matter volume in patients experiencing SUDEP and high-SUDEP-risk patients, setting the stage for possible autonomic and respiratory output dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated submillimeter precision, 83,84 thus enabling high‐fidelity targeting in compact, highly eloquent regions. One such location could be the anterior nucleus of the thalamus, which is the current target for deep brain stimulation 73 . Other potential applications would be the acoustic ablation of amygdala, hippocampus, and piriform cortex for temporal lobe epilepsy, or ablation of lesional tissues such as focal cortical dysplasia, periventricular heterotopia, tuber, hypothalamic hamartoma, and small neoplasm 85‐87 .…”
Section: Future Directions: High Intensity Focused Ultrasound (Hifu)mentioning
confidence: 99%
“…This response seemed to be independent of lobe and 15% of the patients had seizure‐free periods greater than 1 year 70 . Furthermore, there did not appear to be neuropsychological decline, and there was quality of life improvement, decreased sudden unexpected death in epilepsy (SUDEP) rates, and real potential to serve as a tool for long‐term chronic monitoring 71‐73 . RNS‐like systems could also be used to document the effectiveness of anti‐epileptic medication 74 .…”
Section: Introductionmentioning
confidence: 99%
“…Bei zwei Drittel der Menschen mit Epilepsie kann durch konsequente Antikonvulsivaeinnahme dauerhafte Anfallsfreiheit erreicht werden. Im verbleibenden Drittel sollten auch nicht medikamentöse, an Epilepsiezentren angebotene Verfahren wie die resektive Epilepsiechirurgie als effektivste Therapieoption, aber auch die Neurostimulationsverfahren oder ketogene Diäten erwogen werden, zumal all diese Verfahren eine Reduktion der Anfalls-häufigkeit und der SUDEP-Rate im Menschen [67,68] oder im Tiermodell gezeigt haben [69]. Eine Aufklärung der betroffenen Patienten und ihrer Betreuungspersonen über das Risiko von SUDEP und der Rolle der Pharmakoadhärenz in der Risikominderung wurde mittlerweile in die Leitlinien der Deutschen Gesellschaft für Neurologie (DGN) aufgenommen [70].…”
Section: Risikoeinschätzung Prävention Und Aufklärungunclassified